Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Given the functions [tex]\( u(x) = -2x^2 + 3 \)[/tex] and [tex]\( v(x) = \frac{1}{x} \)[/tex], we need to determine the range of the product function [tex]\( (u \cdot v)(x) \)[/tex].
First, let's define the product function [tex]\( (u \cdot v)(x) \)[/tex]:
[tex]\[ (u \cdot v)(x) = u(x) \cdot v(x) = \left(-2x^2 + 3\right) \cdot \left(\frac{1}{x}\right) = \frac{-2x^2 + 3}{x} \][/tex]
To simplify:
[tex]\[ (u \cdot v)(x) = \frac{-2x^2 + 3}{x} = -2x + \frac{3}{x} \][/tex]
Next, we need to analyze the range of the function [tex]\( -2x + \frac{3}{x} \)[/tex].
We can examine the behavior of this function as [tex]\( x \)[/tex] approaches different values:
1. As [tex]\( x \)[/tex] approaches 0 from the positive side ([tex]\( x \to 0^+ \)[/tex]):
[tex]\[ -2x \to 0 \text{ and } \frac{3}{x} \to +\infty \][/tex]
Therefore, [tex]\( -2x + \frac{3}{x} \to +\infty \)[/tex].
2. As [tex]\( x \)[/tex] approaches 0 from the negative side ([tex]\( x \to 0^- \)[/tex]):
[tex]\[ -2x \to 0 \text{ and } \frac{3}{x} \to -\infty \][/tex]
Therefore, [tex]\( -2x + \frac{3}{x} \to -\infty \)[/tex].
3. As [tex]\( x \)[/tex] approaches [tex]\( \infty \)[/tex] ([tex]\( x \to \infty \)[/tex]):
[tex]\[ -2x \to -\infty \text{ and } \frac{3}{x} \to 0 \][/tex]
Therefore, [tex]\( -2x + \frac{3}{x} \to -\infty \)[/tex].
4. As [tex]\( x \)[/tex] approaches [tex]\( -\infty \)[/tex] ([tex]\( x \to -\infty \)[/tex]):
[tex]\[ -2x \to +\infty \text{ and } \frac{3}{x} \to 0 \][/tex]
Therefore, [tex]\( -2x + \frac{3}{x} \to +\infty \)[/tex].
From these observations, we see that the function [tex]\( -2x + \frac{3}{x} \)[/tex] can take on any real value. It can approach [tex]\( +\infty \)[/tex] as [tex]\( x \)[/tex] approaches 0 from the positive side or [tex]\( -\infty \)[/tex] as [tex]\( x \)[/tex] approaches 0 from the negative side. It can also go to [tex]\( -\infty \)[/tex] as [tex]\( x \)[/tex] approaches [tex]\( \infty \)[/tex] and to [tex]\( +\infty \)[/tex] as [tex]\( x \)[/tex] approaches [tex]\( -\infty \)[/tex].
Thus, the range of [tex]\( (u \cdot v)(x) \)[/tex] is:
[tex]\[ (-\infty, +\infty) \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{(-\infty, +\infty)} \][/tex]
First, let's define the product function [tex]\( (u \cdot v)(x) \)[/tex]:
[tex]\[ (u \cdot v)(x) = u(x) \cdot v(x) = \left(-2x^2 + 3\right) \cdot \left(\frac{1}{x}\right) = \frac{-2x^2 + 3}{x} \][/tex]
To simplify:
[tex]\[ (u \cdot v)(x) = \frac{-2x^2 + 3}{x} = -2x + \frac{3}{x} \][/tex]
Next, we need to analyze the range of the function [tex]\( -2x + \frac{3}{x} \)[/tex].
We can examine the behavior of this function as [tex]\( x \)[/tex] approaches different values:
1. As [tex]\( x \)[/tex] approaches 0 from the positive side ([tex]\( x \to 0^+ \)[/tex]):
[tex]\[ -2x \to 0 \text{ and } \frac{3}{x} \to +\infty \][/tex]
Therefore, [tex]\( -2x + \frac{3}{x} \to +\infty \)[/tex].
2. As [tex]\( x \)[/tex] approaches 0 from the negative side ([tex]\( x \to 0^- \)[/tex]):
[tex]\[ -2x \to 0 \text{ and } \frac{3}{x} \to -\infty \][/tex]
Therefore, [tex]\( -2x + \frac{3}{x} \to -\infty \)[/tex].
3. As [tex]\( x \)[/tex] approaches [tex]\( \infty \)[/tex] ([tex]\( x \to \infty \)[/tex]):
[tex]\[ -2x \to -\infty \text{ and } \frac{3}{x} \to 0 \][/tex]
Therefore, [tex]\( -2x + \frac{3}{x} \to -\infty \)[/tex].
4. As [tex]\( x \)[/tex] approaches [tex]\( -\infty \)[/tex] ([tex]\( x \to -\infty \)[/tex]):
[tex]\[ -2x \to +\infty \text{ and } \frac{3}{x} \to 0 \][/tex]
Therefore, [tex]\( -2x + \frac{3}{x} \to +\infty \)[/tex].
From these observations, we see that the function [tex]\( -2x + \frac{3}{x} \)[/tex] can take on any real value. It can approach [tex]\( +\infty \)[/tex] as [tex]\( x \)[/tex] approaches 0 from the positive side or [tex]\( -\infty \)[/tex] as [tex]\( x \)[/tex] approaches 0 from the negative side. It can also go to [tex]\( -\infty \)[/tex] as [tex]\( x \)[/tex] approaches [tex]\( \infty \)[/tex] and to [tex]\( +\infty \)[/tex] as [tex]\( x \)[/tex] approaches [tex]\( -\infty \)[/tex].
Thus, the range of [tex]\( (u \cdot v)(x) \)[/tex] is:
[tex]\[ (-\infty, +\infty) \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{(-\infty, +\infty)} \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.